Construction d'un dispositif d'évaluation des enseignements et des formations : le point de vue des apprenants - Christine Gangloff; Marc Weisser; Saloua Bennaghmouch; Sondess-Be (Université de Provence, 2009)
One of the main missions of French university is to evaluate students. But the requirement to assess also training systems is gradually growing. The goal is, on the one hand, to improve the quality of courses and training, and, on the other hand, to allow the comparison of educational systems. In this context, our research consists in collecting the students' point of view about the quality standards they look for during their training. We organized interviews using the methodology of focus groups. We questioned a representative panel of students: general training / vocational training; UFR / IUT / Schools of Engineers; at the beginning of their training / at the end of their training. Then, we identified the constant positions from one group to another, as well as complementary opinions.